Inference making skill in children with visual impairments. (September 2020) - Sullivan, Susan; Oakhill, Jane
Abstract: There is a scarcity of research examining the reading comprehension skills of partially-sighted children despite evidence indicating that they lag behind their typically-sighted (TS) peers in reading comprehension ability. We compare the performance of children with visual impairments (VIs) with that of chronological-age matched TS counterparts on a task that requires them to make emotional, temporal and spatial inferences from short texts. The findings indicate that children with VIs exhibit a specific deficit in drawing inferences about spatial information in narratives as opposed to emotional or temporal information. The results are discussed in relation to the role of visual acuity in imagery skills and how this affects the construction of a mental model of a text.